Respuesta :
To reflect across the x axis, you would make the original equation negative.
The answer would be: g(x)=−2|x|
Answer: [tex]g(x)=-2|x|[/tex]
Step-by-step explanation:
When a function [tex]y=f(x)[/tex] is reflected over x-axis then it actually flip itself around x-axis and gives a mirror image of the original function.
The new function will be [tex]y=-f(x)[/tex]
Given : The graph of g(x) is obtained by reflecting the graph of [tex]f(x)=2|x|[/tex] over the x-axis.
Then , g(x) should be
[tex]g(x)=-f(x)=-(2|x|)=-2|x|[/tex]
Therefore, the equation describes g(x) would be
[tex]g(x)=-2|x|[/tex]